A complex phylogeny of lineage plasticity in metastatic castration resistant prostate cancer - Jones T. Nauseef; Timothy R. Chu; William F. Hooper; Alicia Alonso; Ali Oku; Heather Geiger; Zoe R. Goldstein; Minita Shah; Michael Sigouros; Jyothi Manohar; Zoe Steinsnyder; Lara Winterkorn; et al. (npj Precision Oncology)
Abstract Aggressive variant and androgen receptor (AR)-independent castration resistant prostate cancers (CRPC) represent the most significant diagnostic and therapeutic challenges in prostate cancer. This study examined a case of simultaneous progression of both adenocarcinoma and squamous tumors from the same common origin. Using whole-genome and transcriptome sequencing from 17 samples collected over >6 years, we established the clonal relationship of all samples, defined shared complex structural variants, and demonstrated both divergent and convergent evolution at AR. Squamous CRPC-associated circulating tumor DNA was identified at clinical progression prior to biopsy detection of any squamous differentiation. Dynamic changes in the detection rate of histology-specific clones in circulation reflected histology-specific sensitivity to treatment. This dataset serves as an illustration of non-neuroendocrine transdifferentiation and highlights the importance of serial sampling at progression in CRPC for the detection of emergent non-adenocarcinoma histologies with implications for the treatment of lineage plasticity and transdifferentiation in metastatic CRPC.